2013
DOI: 10.1002/grl.50348
|View full text |Cite
|
Sign up to set email alerts
|

High biolability of ancient permafrost carbon upon thaw

Abstract: Ongoing climate warming in the Arctic will thaw permafrost and remobilize substantial terrestrial organic carbon (OC) pools. Around a quarter of northern permafrost OC resides in Siberian Yedoma deposits, the oldest form of permafrost carbon. However, our understanding of the degradation and fate of this ancient OC in coastal and fluvial environments still remains rudimentary. Here, we show that ancient dissolved OC (DOC, >21,000 14C years), the oldest DOC ever reported, is mobilized in stream waters draining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
345
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 270 publications
(390 citation statements)
references
References 38 publications
35
345
10
Order By: Relevance
“…The narrow ratios, especially for the DOC fraction in the mudpool and transition zone, reflect the high mineralization rates of OM. DOC/DN-ratios in the thaw stream are extremely low (4) indicating strong mineralization, which is typical for aerobic streams draining permafrost areas Vonk et al, 2013). However, in contrast to C/Nratios, degradation is not reflected by δ 13 C-TOC and δ 13 C-DOC signatures, which did not change considerably in the disturbed zone.…”
Section: Processes After Initial Slumpingmentioning
confidence: 95%
See 1 more Smart Citation
“…The narrow ratios, especially for the DOC fraction in the mudpool and transition zone, reflect the high mineralization rates of OM. DOC/DN-ratios in the thaw stream are extremely low (4) indicating strong mineralization, which is typical for aerobic streams draining permafrost areas Vonk et al, 2013). However, in contrast to C/Nratios, degradation is not reflected by δ 13 C-TOC and δ 13 C-DOC signatures, which did not change considerably in the disturbed zone.…”
Section: Processes After Initial Slumpingmentioning
confidence: 95%
“…It is of particular importance for the mobilization of OM, as it triggers its release by disturbing the frozen ground Bowden et al, 2008;Vonk et al, 2013). Thermokarst in upland, inland, sub-Arctic, and High Arctic permafrost regions, was intensively studied focusing on the lability of permafrost carbon, greenhouse gas emissions, release of nutrients (e.g., nitrogen, phosphorus, sulfur), and impacts on aquatic systems Cassidy et al, 2016;Frey et al, 2007;Turetsky et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that Arctic watersheds may increasingly augment the role of freshwater ecosystems in the global flux of terrestrial carbon to the atmosphere (Walter et al, 2006;Denfeld et al, 2013;Vonk et al, 2013;Hayes et al, 2014;Spencer et al, 2015) and ocean (Frey and Smith, 2005;Frey and McClelland, 2009;Schreiner et al, 2014;Tesi et al, 2014) as a result of climate warming and changing regional hydrology. Terrestrial sources of organic matter generally dominate the energy and carbon fluxes through stream, riverine, and estuarine ecosystems (Mulholland, 1997;Holmes et al, 2008), but the lability and composition of this carbon remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…A stepwise freshet may lead to a more complex transition between base flow and freshet DOC. Furthermore, the lack of extensive permafrost in the Fraser basin excludes significant inputs from a potential pool of relatively degraded and aged soil DOC during late spring and summer months (Neff et al, 2006;Raymond et al, 2007;Wickland et al, 2007;O'Donnell et al, 2010), though this DOC is often found to be labile Vonk et al, 2013). In small streams, on the other hand, storm-driven discharge events are short-lived and may deliver fresh DOC to stream channels more efficiently than the long, relatively gradual rising limb of the spring freshet in the Fraser.…”
Section: Biogeochemical Dynamics Of Doc Have Not Previously Been Invementioning
confidence: 99%